P842 Healthcare engagement and HPV vaccination among gay, bisexual, and other men who have sex with men (gbMSM): a CIRN study. (14th July 2019) - Grewal, Ramandip; Yeung, Anna; Brisson, Marc; Grennan, Troy; Pokomandy, Alexandra De; Cox, Joseph; Lambert, Gilles; Moore, David; Coutlée, François; Deeks, Shelley; Gardner, Sandra; Griffiths, Dane; et al.
Abstract : Background: Canada was one of the first countries to offer publicly funded programs providing HPV vaccine free of charge to gbMSM. In 2015–2016, the provinces of British Columbia (BC), Ontario (ON), and Quebec (QC) implemented programs for gbMSM aged 9–26 years. We sought to explore where men received the HPV vaccine and the influence of healthcare engagement on vaccination. Methods: Engage is a sexual health study among gbMSM aged 16+ in the largest urban centres in each province: Vancouver, BC; Toronto, ON; and Montreal, QC. Men are recruited via respondent driven sampling (RDS). We compared proportions (non-RDS adjusted) to questionnaire responses on healthcare engagement among vaccinated (1+ doses) versus unvaccinated in the subset of men aged ≤26 years old at enrolment. Results: From 01/2017 to 31/12/2018, 477 men aged ≤26 enrolled (144 Vancouver, 84 Toronto, 249 Montreal). Their median age was 24 years (IQR 22–25). In Vancouver, Toronto and Montreal, respectively, 48.6%, 44.1%, 44.2% had initiated HPV vaccination with 58.6%, 56.8% and 48.2% of vaccinated men having received all 3 doses. Popular venues for vaccination included a: sexual health clinic (50.7%), medical clinic not specializing in sexual health (14.8%), community health centre (10.6%), and doctor's office (7.4%). Compared to unvaccinated men, more vaccinated men had a family doctor (65.9% vs 52.3%, p=0.0047), had a different provider/clinic for sexual health care or had a HIV care provider (66.8% vs 51.8%, p=0.0022), had a STI/HIV test in the past year (90.8% vs 68.6%, p<0.0001), and were diagnosed with a STI in the past year (39.6% vs 20.0%, p<0.0001). Conclusion: Compared to unvaccinated men, vaccinated men were more engaged in healthcare. It is unknown whether men requested the vaccine or providers offered it. Nevertheless, our findings suggest opportunistic HPV vaccination when men receive other services, particularly those related to sexual health. Disclosure: No significant relationships.